THE IMPACT OF DIGITAL MARKETING SYSTEM ON MSMES IN MEDAN CITY: A CASE STUDY OF PT. KELORIA MORINGA JAYA - Afandi, Ahmad (Proceeding International Seminar of Islamic Studies, 2023)
This simple research aims to explore the impact of digital marketing systems on MSMEs in Medan City in increasing product sales and evaluating user satisfaction with affiliatebased websites developed for PT. Keloria Moringa Jaya. The research method was a questionnaire survey, with nine questions to 100 respondents. Based on respondents' responses, it was concluded that the use of websites and affiliate marketing in digital marketing could positively contribute to increasing MSME sales. This can be seen from the data analysis results showing a positive correlation between the use of affiliate marketing websites and the increase in respondents' interest in becoming affiliate marketing and marketing MSME products. The research results are expected to help MSMEs in Medan City understand the benefits of digital marketing and how to apply it effectively in their business.